Genetic disposition and modifiable factors independently associated with anemia in patients with type 2 diabetes mellitus. Issue 1 (April 2015) - Chiou, Terry Ting-Yu; Lee, Jong-Jer; Wang, Ming-Chung; Chung, Min-Shien; Pan, Lin-Lin; Hsieh, Ching-Jung; Huang, Siang-Ting; Chang, Hsueh-Wen; Yang, Kuender D.; Lee, Chien-Te; Liu, Rue-Tsuan
Highlights EPO promoter polymorphism is associated with anemia in patients with type 2 diabetes. ACE Insertion/Deletion and TNF-a G-308A were not associated with anemia. Other risk factors: Age, duration of diabetes, renal function, and albuminuria. TT and TG genotypes in EPO were associated with 3–5-fold increased anemia risk. The EPO genotype may help identify patients at risk of anemia.